Classification of filled joint based on the characteristics of its constitutive components - Mohd. Amin, Mohd. For; Kassim, Azman; Mohamad, Edy Tonnizam; Ong, Heng Yau (Universiti Teknologi Malaysia, 2003)
Filled joints in rock mass pose a number of constructional problems. When filled joints are reckoned to be critical to an engineering structure, their behaviours are often studied using expensive in-situ testing and complex full-scale physical modelling. This is because sampling of an undisturbed filled joint is almost impossible to undertake. As such, a means of anticipating the behaviour and characteristics of this critical geological discontinuity is important. One method to predict the behaviour of filled joint is through systematic classification based on its essential components, particularly those features that control the behaviour of the joint under shear and compressive load. Exposed filled joints in granite rock in Lahat, Perak, have been selected for the field study. The field assessments indicate there are several components of filled joint that exhibit certain geological and mechanical characteristics which can be identified and assessed in the field and laboratory. For the infilling material, the essential features include thickness, weathering grade and texture. For the host joint blocks, the features include texture and roughness of the joint surface and weathering degree of the blocks. The weathering grade of the infill and joint blocks are geological characteristics that can be graded according to the standard classification system. The samples of infilling were further evaluated in the laboratory using index and characterisation tests like sieving, compression and shear tests. This study has shown that there are several essential components of filled joint that can be used to predict its behaviour. These components can be easily characterised and evaluated in the field and laboratory. The characteristics of the infilling material and roughness of joint surface are among the features that control the behaviour of filled joint, and subsequently can be used as classification index for predicting the joint behaviour.